Pandangan Hukum Islam terhadap Fenomena Penggunaan Kata “Anjay” dalam Pergaulan Remaja - Fuadi Isnawan (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2021)
This study focuses on the association of today's teenagers with increasingly complex and diverse relationships in their daily interactions. This complex interaction spawned a new culture in communication, namely using swear words in responding to certain things. One of the popular words is the word "anjay" which is a derivative of the word "dog". The word dog that has a negative connotation is changed to the word "anjay" which has a more subtle meaning than the word dog. The word "anjay" is usually used by teenagers to express awe, amazement, joy and surprise. Unlike the word dog which is more often used for swearing. The method used is a literature study that will discuss social etiquette and ethics in communicating in Islam. and politeness in society. It is not permissible to use the word even in a good and not negative sense. In addition to conflicting with social etiquette, the word "anjay" will also conflict with the ethics of communication in Islam which upholds nobility in every word that exists, such as the principles of Qaulan Layyina, Qaulan Karima and Qaulan Ma'rufa